Do contexto da influência ao contexto da prática: caminhos percorridos para a implementação da Lei nº 10.639/03 nas escolas municipais de Esteio-RS - Chagas, Wagner dos Santos (Universidade do Vale do Rio do Sinos, 2010)
The research investigates how the anti racism policy (Federal Law 10.639/03) was put into context by the municipal teaching body of Esteio, represented by the Group of African Study in the period of 2003 to 2008. The goal is to analyze how the Federal law nº 10.639/03 was adapted and put into the practice by a study group composed by teachers from the municipal education system of Esteio. Theoretically, the research follows a critic paradigm developed by the following theorists: Gramsci, Freire, McLaren, Pacheco, Triviños, Munanga, Baa, and others. In terms of methodology, the orientation is to value qualitative aspects using tools to collect data empirically such as documents analyzes, semi structured interviews, and field diaries or journals. Three professors collaborated with the study. Their selection was due to the fulfillment of established criterions. In the data analysis’ process, four categories were identified: The movement responsible for the group creation, Political Formation and Educational
Keywords: ações afirmativas; ciclo de políticas; Lei Federal nº 10.639/03; affirmative action; cycle of policies; Federal Law nº 10.639/03; Ciências Humanas